Performance optimization in dye-sensitized solar cells with β-NaYF4:Yb3+, Er3+@SiO2@TiO2 mesoporous microspheres as multi-functional photoanodes. (1st September 2016) - Wang, Yuanwei; Zhu, Yihua; Yang, Xiaoling; Shen, Jianhua; Li, Xueqin; Qian, Shaohong; Li, Chunzhong
Graphical abstract: Highlights: NaYF4 @SiO2 crystalsareembeddedintoTiO2 mesoporousmicrospheressimplily. (*). Single-crystal-likeTiO2 mesochannels can increase conductivity and dye adsorption. NaYF4 @SiO2 crystals can increase NIR light upconversion harvest. N@S@T microspheres can increase light scattering. The η of the DSSCs with N@S@T-150 is 9.10%, increased by 26.39%. Abstract: The β-NaYF4 :Yb 3+, Er 3+ @SiO2 @TiO2 (N@S@T) mesoporous microspheres have been successfully synthesized via a simple evaporation-driven oriented assembly method (EDOA) and applied as multifunctional photoanode films on top of commercial P25 layers in dye-sensitized solar cells (DSSCs). Structural characterizations indicated that N@S@T mesoporous microspheres consisted of uniform β-NaYF4 :Yb 3+, Er 3+ nanocrystals, SiO2 insulating middle shell and single-crystal-like anatase TiO2 shell exposed with (101) facets. Studies revealed that introducing β-NaYF4 :Yb 3+, Er 3+ @SiO2 into TiO2 mesoporous microspheres would remarkably enhance the short-circuit current density ( Jsc ). The SiO2 insulating middle shell played an role in packaging upconvertion nanoparticles (UCNPs) into TiO2 mesoporous microspheres, which were constructed to effectively transfer photoinduced electrons and adsorb more dye molecules, benefitting from their high specific surface areas. DSSCs with the optimal doping amount of UCNPs exhibited the Jsc value of 14.95 mA cm −2 and conversion efficiency of 9.10%, which was a notable enhancement of 26.39% in efficiency compared with commercial P25 based DSSCs. Our work demonstrated that introducing N@S@T into photoanodes was an effective method of improving the overall performance of DSSCs.